TRANSMISI HARGA KOPI ARABIKA GAYO DI PROVINSI ACEH - Noratun Juliaviani; Sahara Sahara; Ratna Winandi (Jurnal Agribisnis Indonesia, 2017)
ABSTRACTThe objective of this study is to analyze the price transmission of Gayo Arabica coffee from farmers to exporters. This study utilizesECM (error Correction Model) to investigate price transmission based on monthly price data in farmer and exporter level from Januari 2008 until December 2014. The result showed that price transmission test ECM-EG model showed that in short term, the price transmission is assymetric and symetric in long term.The symmetrical price transmission between farmers and exporters in the long term, showed that there was no misuse of market power, Therefore, price changes that occur at the farmer level in the long term were transmitted perfectly towards exporter. Asymmetric price transmission in the short term is commonly caused by cost adjustment factors and marketing agency behaviors in the pricing mechanism and the performance of each level / marketing agencies. Therefore, the need for setting prices of Gayo Arabica coffee, especially at the producers (farmers) level and the government's role in monitoring the price according to the quality of coffee, and inform the development of the market price (the local and the world) to the farmers.